The relationship between corporate governance attributes and firm performance - Alhaji, Idris Adamu (2012)
A number of studies, particularly in developed countries, had been carried out to explore the relationship between corporate governance and firm performance. Since, the value creation of corporate governance can be measured through the firm performance, corporate governance act as a mechanism to align management's goals with the stakeholders especially to increase firm performance. Despite extensive study of corporate governance there are still inconsistencies in the link between corporate governance and firm performance. Therefore, the aim of this research is to explore the relationship between corporate governance attributes and firm performance in Malaysia Public Listed Companies. To do so five corporate governance components was used as independent variables include: Independent director, board size, audit committee, leadership structure and board meeting. While the dependent variables are two firm performance measurements; return on equity (ROE) and earning per share (EPS). Based on a random stratified sampling eight hundred thirty one (831) listed companies from main board of Bursa Malaysia for the year 2009, 2010 and 2011 were selected as samples of the study. The data gathered from Annual Reports of the companies have been entered into Excel Spread Sheet, then were analyzed using Statistical Package for the Social Sciences (SPSS) program. Three types of data analyses have been performed; descriptive, T-test and Spearman correlation. The study discovered that, independent non-executive directors has an influence on earnings per share, board size has an influence on return on equity and earnings per share and also audit committee has an influence on earnings per share, leadership structure has an influence on return on equity and board meeting also has an influence on earnings per share. The results on the relationship between the firm performance and corporate governance mechanism suggest a positive relationship between return on equity and earnings per share as per the hypothesis testing. Therefore, the results also show that good corporate governance enforcement influence firm performance. Finally, no single theory offers a complete explanation of board characteristics-firm performance relationship, but rather rudiments of each theory can be seen to apply in different situations.